Analysis of Cost Reduction Techniques Adopted in Hospitals in and Around Pune. (December 2014) - Kulkarni, Meenal; Pandit, Anil
Purpose: The purpose of this study is to analyze the various techniques implemented with respect to cost reduction in privately owned hospitals in and around Pune. Design/Methodology/Approach: A total of 30 privately owned hospitals were randomly selected for the purpose of the study. The methodology comprised administering the questionnaire along with a personal interview with the administrative/finance officer. The hospitals included for the study were selected based on the following characteristics: Hospitals with capacity of 50–100 beds were termed as small hospitals and hospitals with more than 100 beds were termed as large hospitals. Further they were segregated as general hospitals (<100 beds) and speciality and super speciality hospital in multiple urban locations. These organizations were for-profit hospitals. Findings: The results predominantly highlight the key techniques required to be used by most of the hospitals as the cost reduction method, and also the various aspects on which improvement and further development is required to keep on providing better health care service delivery with effective cost containment in the city of Pune.